2003
DOI: 10.1890/02-5283
|View full text |Cite
|
Sign up to set email alerts
|

Feedbacks Between Soil Nutrients and Large Herbivores in a Managed Savanna Ecosystem

Abstract: Small-scale fertilization experiments have shown that soil nutrients limit plant productivity in many semiarid grasslands and savannas, but linkages among nutrients, grasses, and grazers are rarely studied in an ecosystem context. We used hectare-scale heterogeneity in soil nutrients created by cattle management practices within a geologically homogeneous savanna to examine relationships among soil nitrogen and phosphorus, aboveground net primary production (ANPP), grass nutrient content, and a mixed community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
229
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(256 citation statements)
references
References 63 publications
16
229
11
Order By: Relevance
“…First, nutrient-enriched patches created by abandoned cattle bomas can persist for decades to centuries and provide a key source of nutrient-rich forage for both native and domestic grazers. Nutrient-rich glades that develop from abandoned bomas in the red sands habitat not only sustain local impala abundance but are also maintained as glades by nitrogen inputs from impala (Augustine et al, 2003). Such feedbacks and interactions among cattle bomas, soil and plant nutrients, and wild ungulates indicate that ranch managers can influence the long-term distribution and abundance of wild ungulates though the placement and rotation of current bomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, nutrient-enriched patches created by abandoned cattle bomas can persist for decades to centuries and provide a key source of nutrient-rich forage for both native and domestic grazers. Nutrient-rich glades that develop from abandoned bomas in the red sands habitat not only sustain local impala abundance but are also maintained as glades by nitrogen inputs from impala (Augustine et al, 2003). Such feedbacks and interactions among cattle bomas, soil and plant nutrients, and wild ungulates indicate that ranch managers can influence the long-term distribution and abundance of wild ungulates though the placement and rotation of current bomas.…”
Section: Discussionmentioning
confidence: 99%
“…Soil nitrogen can be lost from glades over time via several pathways, including leaching, denitrification, and volatilization, such that long-term glade persistence likely depends upon nitrogen inputs to replenish these losses. Detailed analysis of glade nitrogen budgets at MRC showed that during dry seasons, impala bed within glades (Figure 6) while foraging in adjacent bushland, causing a substantial net input of nitrogen via dung and urine deposition (Augustine et al, 2003). This N input may facilitate long-term glade persistence in the Cynodon-dominated state and represents a pathway by which impala benefit all ungulate grazers that make use of glades, including livestock.…”
Section: Long-term Glade Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Herbaceous species were clearly edible to arthropods in highproductivity blocks, as shown by the increase in arthropod abundance with increasing herbaceous productivity and percent cover. Moreover, there is a well established relationship between primary productivity and ungulate consumption rates in rangelands (29), which argues against the hypothesis that plants overall were less palatable in the high-productivity sites. However, we cannot conclusively rule out the latter scenario for the direct effect of ungulates on tree density (and hence for the treedensity-mediated component of the indirect effect of ungulates on lizards).…”
Section: Discussionmentioning
confidence: 99%
“…ref. 28, dissolved organic nitrogen pump) or net nitrogen transfer by large herbivores from nutrient-poor to nutrient-rich grasslands in the Serengeti (30). Abiotic factors can also induce plantunavailable paths of nutrient loss.…”
Section: What Determines Propensity For Plant-unavailable Loss?mentioning
confidence: 99%